2018
DOI: 10.1007/s40292-018-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter-arm Systolic Blood Pressure Difference in Physically Active, Adult Subjects

Abstract: The prevalence of ΔPsys ≥ 10 mmHg in this population was only slightly lower than what observed in older, hypertensive or diabetic patients. Cases and Controls did not differ in physical activity level, ankle brachial pressure index and CV risk. However, low test-retest reliability might limit the use of ΔPsys as a reliable marker for CV screening in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…It is like Donfrancesco's study, which involved young, healthy smoker Italian adults [24]. In Daniel's study, there was no signi cant IAD associated with smoking and hypertension [25]. Our study shows a signi cant difference associated with smoking and high blood pressure; (P <.001 and P <.001, respectively).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is like Donfrancesco's study, which involved young, healthy smoker Italian adults [24]. In Daniel's study, there was no signi cant IAD associated with smoking and hypertension [25]. Our study shows a signi cant difference associated with smoking and high blood pressure; (P <.001 and P <.001, respectively).…”
Section: Discussionsupporting
confidence: 64%
“…Verberk's meta-analysis showed that the IABPD should be measured precisely because this concurrent checking of BP in both arms is required [42]. Daniel recommends measuring blood pressure in the arm with higher blood pressure to diagnose potential hypertension [25]. However, this cross-sectional study was conducted with young, healthy adults who are apparently stable, Because of a lack of long-term follow-up; we could not conclude on the longterm effects of these results.…”
Section: Discussionmentioning
confidence: 96%
“…Adiposity may be an important predictor and modifiable risk factor for inter‐arm blood pressure differences, with a large potential impact in public health. It may be worth assessing IABPD in healthy individuals with adiposity, since the prevalence of IASBPD ≥ 10 mm Hg in a young, healthy, and physically active population of adults was only slightly lower than that observed in older, hypertensive, or diabetic patients . Also, results from another study suggested that the clinical impact of IASBPD was more prominent in patients without underlying diseases like hypertension, diabetes, or obesity, than in patients with these diseases .…”
Section: Discussionmentioning
confidence: 99%
“…It may be worth assessing IABPD in healthy individuals with adiposity, since the prevalence of IASBPD ≥ 10 mm Hg in a young, healthy, and physically active population of adults was only slightly lower than that observed in older, hypertensive, or diabetic patients. 3 Also, results from another study suggested that the clinical impact of IASBPD was more prominent in patients without underlying diseases like hypertension, diabetes, or obesity, than in patients with these diseases. 8 If the results of our study are corroborated in additional populations, simultaneous blood pressure measurement in both arms could be recommended routinely in clinical practice to help predict the development of future cardiovascular complications for high-risk individuals.…”
Section: Conclusion and Implications For Practice And Future Researchmentioning
confidence: 99%
See 1 more Smart Citation